LAS ORDENANZAS EN GOBIERNOS LOCALES RESIDENCIALES SOBRE EL COMERCIO AMBULATORIO, SE CONSTITUYEN EN NORMA LEGAL EXCLUYENTE QUE COADYUVA A LA GENERACIÓN DE POBREZA, PUDIENDO APROVECHARSE COMO INCLUSIVA POR ASOCIATIVIDAD. - Barreda Guerra, Juan Manuel (2012)
In our national democratic system every district of our country enjoys political autonomy, economic, social, cultural and technological, but we can see that, in the aspect of economic power in the City Council District, will have exclusive municipal ordinances such as the ban street vending, thus wasting opportunities organized to contribute to the fight against poverty, and this is a national problem that we all face. These ordinances alienate certain vulnerable groups of beneficial economic potential market area in which these vulnerable groups properly organized with guidance and support of local residential, can meet a variety of needs entrepreneurially residential markets, which everyone can benefit, ie state, vulnerable groups and the residential market.